2014
DOI: 10.1016/j.jcdr.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of cardiovascular drug utilization in coronary care unit patients of a tertiary care hospital

Abstract: a b s t r a c tBackground: A wide variation exists in the patterns of pharmacotherapy among patients admitted with cardiovascular diseases. Very few studies have evaluated the potential determinants of drug utilization. Our objective was to evaluate the clinical characteristics and patterns of cardiovascular drug utilization among patients in coronary care unit (CCU) and assess the determinants of cardiovascular drug use among patients with coronary artery disease (CAD). Methods: In this retrospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
(24 reference statements)
8
9
0
Order By: Relevance
“…For 2015, of the total 540 patients, 168 patients (31%) were hypertensive, 82 patients (15%) were diabetic and 112 patients (21%) were found to have both HTN and DM, while 178 patients (33%) neither had HTN or DM associated with IHD, and for 2013, of the total 410 patients, 104 patients (25%) were hypertensive, 65 patients (16%) were diabetic and 82 patients (20%) were found to have both HTN and DM, while 159 patients (39%) neither had HTN or DM associated with IHD. This result is similar to a study done by George et al 20 Prevalence of hypertension in India, for the last three decades, has increased by about 30 and 10 times among urban and rural residents respectively. 23 Hypertension and diabetes mellitus are major and modifiable risk factors which when controlled can significantly reduce IHDs morbidity and mortality.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For 2015, of the total 540 patients, 168 patients (31%) were hypertensive, 82 patients (15%) were diabetic and 112 patients (21%) were found to have both HTN and DM, while 178 patients (33%) neither had HTN or DM associated with IHD, and for 2013, of the total 410 patients, 104 patients (25%) were hypertensive, 65 patients (16%) were diabetic and 82 patients (20%) were found to have both HTN and DM, while 159 patients (39%) neither had HTN or DM associated with IHD. This result is similar to a study done by George et al 20 Prevalence of hypertension in India, for the last three decades, has increased by about 30 and 10 times among urban and rural residents respectively. 23 Hypertension and diabetes mellitus are major and modifiable risk factors which when controlled can significantly reduce IHDs morbidity and mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Polypharmacy may be justified as this was a tertiary care setting where the majority of patients were hospitalized with multiple co-morbidities. This result was similar to the finding by George et al 20 Duration of stay at the hospital varied from patient to patient and their associated conditions. In our study for the year 2015, the average number of days spent by the patients in the hospital was 3.51 and that in 2013 was 3.59 days.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Polypharmacy may be justified as this was a CCU setup where the majority of patients were hospitalized with multiple co morbidities. This result was similar to the finding by George et al 15 Comparing 2010 with 2016 shows average number of drugs per prescription is increased in prospective study.…”
Section: Discussionsupporting
confidence: 91%
“…Among other findings, the researchers concluded that antiplatelets were an integral component of treatment of certain CVDs. 8 The current study also indicated a high and significant usage of antiplatelet medications.…”
Section: Discussionsupporting
confidence: 56%